2017
DOI: 10.1084/jem.20170335
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell and antigen dispersal landscapes regulate T cell immunity

Abstract: Gerner et al. show that spatial compartmentalization in lymph nodes of DCs specialized for MHC I versus MHC II presentation determines the amount of antigen these cells capture after immunization and regulates the relative generation of CD4+ versus CD8+ T cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 79 publications
7
162
1
1
Order By: Relevance
“…Furthermore, quantitative analysis of resident cDC1 and cDC2 organization recapitulated previous findings, with preferential localization of resident cDC2 in the LN periphery and with more heterogeneous distribution of resident cDC1s across different LN compartments, including the T cell zone and some presence in the LN medulla. 4,5,[7][8][9]44,56 Intriguingly, as revealed by 3D vascular based neighborhood analysis, we found that both resident cDC1 and cDC2 subsets were also highly associated with LN blood vessels. Given the spatial segregation of these DC populations to different LN regions, we found that resident cDC1s and cDC2s were also associated with distinct vascular trees, with little local intermixing.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, quantitative analysis of resident cDC1 and cDC2 organization recapitulated previous findings, with preferential localization of resident cDC2 in the LN periphery and with more heterogeneous distribution of resident cDC1s across different LN compartments, including the T cell zone and some presence in the LN medulla. 4,5,[7][8][9]44,56 Intriguingly, as revealed by 3D vascular based neighborhood analysis, we found that both resident cDC1 and cDC2 subsets were also highly associated with LN blood vessels. Given the spatial segregation of these DC populations to different LN regions, we found that resident cDC1s and cDC2s were also associated with distinct vascular trees, with little local intermixing.…”
Section: Discussionsupporting
confidence: 54%
“…[4][5][6][7] Spatial segregation of these functionally distinct DC subsets directly influences the sensitivity, kinetics, magnitude, and quality of T cell responses, thus playing a critical role in the generation of adaptive immunity. 5,8,9 Notably, these findings have only recently been observed in what were previously considered to be relatively well-studied organs, suggesting that high-dimensional imaging approaches can yield important new insights into how complex biological systems operate.…”
Section: Introductionmentioning
confidence: 95%
“…Notably, the association of TMEM176B expression with a subset of cDC2 in Binnewies et al 51 is concordant with our data in the mouse showing that Tmem176a/b are markedly over-expressed in cDC2 compared to cDC1. cDC2 exhibit an overall dominance in MHC II presentation in vivo resulting from the combination of their intrinsic efficiency 28,52 and their favorable position within lymphoid tissues for antigen uptake 53 . Consistently, we found that Tmem176a/b deficiency selectively affected the capacity of DCs to prime naive CD4 + T cells but not CD8 + T cells in vivo.…”
Section: /36mentioning
confidence: 99%
“…These approaches can quantify the number and location of cells throughout a tissue (5), identify cell-cell interactions (6), and correlate protein expression to cellular localization (7). Histo-cytometry and dynamic in situ cytometry have been applied to a variety of imaging systems including confocal (8)(9)(10), epi-fluorescence (11,12), and two-photon microscopy (4). However, these approaches are time consuming due to the need for extensive hands-on image processing.…”
Section: Introductionmentioning
confidence: 99%